Influence of Teams Games Method by Kokami and Learning Motivation on Arabic Language Learning Outcomes / Pengaruh Teams Games Method by Kokami dan Motivasi Belajar terhadap Hasil Belajar Bahasa Arab - Novita Sari; Ahmad Bukhari Muslim; Ahmad Sodiq; Erlina Erlina; Muhammad Sufian (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2024)
This research aims to investigate Influence of Teams Games method by kokami and Learning Motivation ‎on Arabic Language Learning Outcomes in Muhammadiyah Senior High School. The research methodology utilized is quantitative with an experimental approach. The sample consists of tenth-grade students engaged in Arabic language learning. Data is collected through learning outcome tests and observation of the implementation of the Team Games Method by kokami and learning motivation in the learning process. Data analysis determines the extent of the influence of these variables on Arabic language learning outcomes. The results indicate an influence of the Teams Games method by kokami and learning motivation on Arabic language learning outcomes. This is evident from the average pretest scores of 54.79 and posttest scores of 80.20. The impact of the Teams Games method by kokami on Arabic language learning outcomes is 26.8%. Furthermore, the influence of the Teams Games method by kokami on learning motivation is 67.8%, followed by the impact of learning motivation on learning outcomes at 54.0%. The combined effect of the Teams Games method by kokami and learning motivation on learning outcomes is 26.8%. In conclusion, it can be inferred that the Teams Games method by kokami impacts both learning motivation and Arabic language learning outcomes for students at Muhammadiyah Senior High School Bandar Lampung. This research hopes that Arabic language teachers will implement the Teams Games method by kokami to motivate students and improve Arabic language learning outcomes.Abstrak: Penelitian ini bertujuan untuk menyelidiki pengaruh metode Teams Games dengan kokami dan motivasi belajar terhadap hasil belajar bahasa Arab di SMA Muhammadiyah. Metodologi penelitian yang digunakan adalah kuantitatif dengan pendekatan eksperimental. Sampel terdiri dari siswa kelas sepuluh yang terlibat dalam pembelajaran bahasa Arab. Data dikumpulkan melalui tes hasil belajar dan observasi pelaksanaan metode Teams Games dengan kokami serta motivasi belajar dalam proses pembelajaran. Analisis data menentukan sejauh mana pengaruh variabel-variabel ini terhadap hasil belajar bahasa Arab. Hasil penelitian menunjukkan adanya pengaruh metode Teams Games dengan kokami dan motivasi belajar terhadap hasil belajar bahasa Arab. Hal ini terlihat dari skor rata-rata pretest sebesar 54,79 dan posttest sebesar 80,20. Pengaruh metode Teams Games dengan kokami terhadap hasil belajar bahasa Arab adalah 26,8%. Selain itu, pengaruh metode Teams Games dengan kokami terhadap motivasi belajar adalah 67,8%, diikuti oleh pengaruh motivasi belajar terhadap hasil belajar sebesar 54,0%. Pengaruh gabungan metode Teams Games dengan kokami dan motivasi belajar terhadap hasil belajar adalah 26,8%. Kesimpulannya, dapat disimpulkan bahwa metode Teams Games dengan kokami mempengaruhi motivasi belajar dan hasil belajar bahasa Arab siswa di SMA Muhammadiyah Bandar Lampung. Penelitian ini berharap guru bahasa Arab akan menerapkan metode Teams Games dengan kokami untuk memotivasi siswa dan meningkatkan hasil belajar bahasa Arab.